Enhancing Knowledge and Awareness among Vendors in Preventing SO₂ Exposure and Respiratory Disorders in Gas Station Areas - Muhammad Syafii; Agustatius Sitepu; Efrata Sembiring; Fadlilah Widyaningsih; Fitri Ramadani Harahap (JURNAL PENGMAS KESTRA (JPK), 2026)
Air pollution exposure resulting from motor vehicle emissions in the vicinity of gas stations can increase the risk of respiratory disorders among surrounding communities, including vendors who conduct daily activities within these areas. Sulfur dioxide (SO₂) is one of the major air pollutants that may cause respiratory tract irritation, coughing, shortness of breath, and impaired lung function when exposure occurs continuously over a prolonged period. Inadequate awareness regarding the use of personal protective equipment (PPE), particularly face masks, further contributes to the increased risk of adverse health effects among the exposed population. This community service program aimed to enhance the knowledge and awareness of vendors operating around gas stations regarding the health hazards associated with SO₂ exposure and strategies for preventing respiratory disorders. The intervention was implemented through a participatory health education approach, including health counseling sessions, education on proper mask use, mask-wearing demonstrations, interactive discussions, and the distribution of face masks. The results indicated that prior to the intervention, only 12% of participants understood the respiratory health risks associated with SO₂ exposure. Following the educational activities, this proportion increased substantially to 92%. Similarly, only 28% of vendors initially recognized the importance of mask use; however, after receiving education and practical demonstrations, 92% demonstrated an understanding of the importance of wearing masks as a preventive measure. Participants’ awareness of maintaining respiratory health also improved markedly, increasing from 40% before the intervention to 80% after the provision of health education, counseling, and mask-use demonstrations. These findings suggest that participatory health education is effective in improving community knowledge and awareness regarding the prevention of respiratory disorders associated with air pollution exposure. It is recommended that vendors working in gas station areas consistently wear face masks during their daily activities to reduce the risk of SO₂ exposure and protect their respiratory health.